TELAAH ULANG MANHAJ TAHLILI (TAFSIR ANALISIS) - Muhammad Anieg (Kopertais Wilayah X Jawa Tengah, 2014)
Tafsir is the main instrument in an attempt to answer the problems of the people, who must soon discovered the concept or theory. This departs from the question that is often uttered by Hassan Hanafi: